Konsep Garapan Tari “Pembuktian Korban Terakhir” - Putri, Sesty Artika (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research discusses the concept of creating a dance with the theme "Pembuktian Korban Terakhir" which was inspired by a woman named Megi Diale, written in the novel Perempuan Menangis Ke Bulan Hitahm, who really wanted to fight for her rights and justice, even though she was hindered by traditional rules, resident’s village and family. She fought for all of this for women's justice and women's rights. The concept of a dance work is the most important part of a dance work, which provides information to the audience and the individuals involved in it. The concept of a dance work itself is a framework that contains the parts that form a dance work. The concept of a dance work is composed of ideas, title, theme, movements, dancers, floor patterns, make-up, fashion, props, dance music accompaniment and lighting.